PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION(GI)TERHADAPHASIL BELAJAR MATEMATIKA SISWA - Rahayu, Siti (Bappeda Kabupaten Pringsewu, 2018)
This study aims to determine the difference in the average learning outcomes of mathematics between students whose learning using cooperative learning model typeGroup Investigation (GI) with students whose learning using conventional learning on the subject matter of the Circle and to know the average of mathematics learning outcomes of students learning using cooperative learning model of Group Investigation (GI) is higher than students whose learning uses conventional learning. Population in this research is class VIII TA 2014-2015. Sampling was taken by cluster random sampling technique. The research instrument used to obtain data in the form of test while for data analysis is done normality test and homogeneity test. Because the sample comes from normal and homogeneous distributed data then it is continued with t-test. The result of data analysis can be concluded that there is difference of mean result of learning of student mathematics taught by using cooperative learning model of Group Investigation (GI) with average of learning result mathematics of students taught by using conventional learning model and the average of students' mathematics learning outcomes taught by using Group Investigation cooperative modes (GI) is greater than the average of mathematics learning outcomes of students taught using conventional learning models.